1995
DOI: 10.1002/srin.199501094
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus equilibrium between BaO‐BaF2‐MnO fluxes and ferro‐manganese melts

Abstract: The equilibrium distribution ratio of phosphorus between BaO-BaF 2-MnO slags and Mn(62-73%)-Fe-C sat-P melts has been determined for different slag compositions, oxygen partial pressures and at 1573-1673 K. The results showed that with a certain content of BaO in the slags, the phosphorus distribution ratio increased with increasing oxygen partial pressure up to about 10-17 atm. A high oxygen partial pressure resulted in a substantial oxidation of manganese from metal to slag. The phosphate capacity of BaO-BaF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Some recent studies [1,2] have established the ancy and breaks into bubbles due to the hydrostatic head, feasibility of dephosphorization of high carbon ferromangasurface tension, and drag forces. The and transitory contact reactions for the present dephosphorihigh phosphorus content (0.35 to 0.50 pct) of high carbon zation study, which might subsequently help in selecting the ferromanganese originates from the manganese ores, the design parameters that could be of importance for efficient majority of which contain a significant amount (ϳ0.2 pct) phosphorus removal.…”
Section: Injection Of Powders: a Preliminarymentioning
confidence: 99%
See 1 more Smart Citation
“…Some recent studies [1,2] have established the ancy and breaks into bubbles due to the hydrostatic head, feasibility of dephosphorization of high carbon ferromangasurface tension, and drag forces. The and transitory contact reactions for the present dephosphorihigh phosphorus content (0.35 to 0.50 pct) of high carbon zation study, which might subsequently help in selecting the ferromanganese originates from the manganese ores, the design parameters that could be of importance for efficient majority of which contain a significant amount (ϳ0.2 pct) phosphorus removal.…”
Section: Injection Of Powders: a Preliminarymentioning
confidence: 99%
“…Some recent studies [1,2] have established the ancy and breaks into bubbles due to the hydrostatic head, feasibility of dephosphorization of high carbon ferromangasurface tension, and drag forces. However, an increase in permanent contact reaction, at a…”
mentioning
confidence: 99%
“…This anomaly may be attributed to the analytical errors for samples from either the 1400°C or 1450°C experiments. Liu et al (1995) similarly observed lower L p values as the temperature was increased during dephosphorization of FeMn alloy with BaO-containing slags.…”
Section: Phosphorus Partition Coefficient: Effect Of Temperature and ...mentioning
confidence: 66%
“…Factors that may have contributed to the loss of Mn include possible air ingress during the tests and the exposure of the alloys to oxygen during quenching, as Mn has a high affinity for oxygen. Liu et al (1995) observed that the use of CaO, SiO 2 , and CaF 2 to dephosphorize ferromanganese melts resulted in increased Mn losses to the slag. Watanabe et al (1993) reported that MnO in basic slag acts as a diluent which may lessen the basic effect of the slag, reducing the capacity of the slag to remove P from the alloy.…”
Section: Effect Of Changing Mno Content Of Baseline Slagmentioning
confidence: 99%
See 1 more Smart Citation